Proses Perubahan Perilaku Berhenti Merokok: Studi Kualitatif Mengenai Motif, Dukungan Sosial dan Mekanisme Coping - Reskiaddin, La Ode; Supriyati, Supriyati (UI Scholars Hub, 2021)
Introduction. A high number of smokers aligned with smoking cessation eagerness, but not all succeed. Objective. to explore the motive, social support and coping mechanism for smoking cessation Methods. Qualitative research with phenomenology research design. We did the snowball sampling technique and participants’ recruitment via WhatsApp and Purposive sampling. 18 in-depth interviews consisted of 5 participants (1 woman and 4 men) who quit smoking within the past 6 months to 2 years, 4 participants who are quitting smoking (months) and 9 people as significant others. Data validation was through triangulation, member checking and peer debriefing. Results. Social factors are the dominant cause of smoking. Health motives are the main motives for quitting smoking includes emotional and instrumental support Conclusion. Smokers’ motivations to quit due to health reasons such as a better level of health. Non-health reasons are religious prohibition (haram) and cigarette expenses higher than primary (food) expenditure. Research also found cognitive coping such as personal suggestion through mindset change, is one of the strategies to control smoking behavior. Social support as a booster or moderator. Coping is the primary controller in smoking cessation. It’s strengthened by personal willingness. Social support acted a moderator.